2020
DOI: 10.1111/1756-185x.14023
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for progression and prognosis of primary Sjögren’s syndrome‐associated interstitial lung disease in a Chinese population

Abstract: Primary Sjögren's syndrome (pSS) is a chronic systemic autoimmune disease which mainly involves the exocrine glands and may also cause a variety of organ damage. Interstitial lung disease (ILD) secondary to pSS is an important factor leading to decreased quality of life in pSS patients, 1 which has attracted more and more attention from clinicians. Previous studies have shown that advanced age, smoking, C-reactive protein level, positive anti-SSA (Ro) antibody and low level of C3 are associated with developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Several serum biomarkers such as hypoalbuminemia, NLR and increased levels of AST tended to be associated with poor prognosis in our study, although the relationship was not strong. Our results showed that hypoalbuminemia was independently associated with increased mortality in IIM patients, which was similar to data from other studies 7,37 . As described above, albumin has a number of essential physiological effects for normal health 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Several serum biomarkers such as hypoalbuminemia, NLR and increased levels of AST tended to be associated with poor prognosis in our study, although the relationship was not strong. Our results showed that hypoalbuminemia was independently associated with increased mortality in IIM patients, which was similar to data from other studies 7,37 . As described above, albumin has a number of essential physiological effects for normal health 23 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, serum LDH level was higher in the lung‐onset group ( p = .018), and was negatively correlated with TCL (%pred). In addition, hypoproteinemia was a risk factor for the progression of ILD and an independent risk factor for mortality in pSS‐ILD patients 8,41 . In our cohort, the serum level of ALB significantly decreased in both groups.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, hypoproteinemia was a risk factor for the progression of ILD and an independent risk factor for mortality in pSS-ILD patients. 8,41 In our cohort, the serum level of ALB significantly decreased in both groups. HRCT score was negatively correlated with serum ALB.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, it is necessary to further identify those patients who have both imaging pulmonary interstitial changes and high clinical risk. In a study, Xu et al found that extensive lung involvement is an independent risk factor for the progression of ILD in patients with pSS, and hypoproteinemia is an independent risk factor for death in such patients (34). In another study conducted by Kamiya et al, the authors found that lower percentage of forced vital capacity and higher serum Krebs von den Lungen-6 (KL-6) levels are predictors of poor prognosis in patients with pSS-ILD (35).…”
Section: Discussionmentioning
confidence: 99%